A REVIEW ON THE CHEMISTRY AND PHARMACOLOGY OF Rennellia elliptica Korth - Osman, Che Puteh; Ismail, Nor Hadiani (Indonesian Journal of Tropical and Infectious Disease, 2017)
Rennellia elliptica, popularly dubbed as Malaysian Ginseng, is widely used in traditional medicine among the local Jakun community in Endau-Rompin State Park, Pahang, Malaysia. The decoction of the roots is traditionally taken for treatment of body aches, as postpartum tonic, as aphrodisiac and for the treatment of jaundice. In the effort of searching new botanical drugs and drug candidates from tropical rainforest, the team from this laboratory had conducted a sizeable phytochemical and biological screening program of tropical plant at Endau Rompin State Park, Pahang with the help from the indigenous people. R. elliptica showed strong antiplasmodial activity in vitro with the IC50 value of 4.04µg/mL. The comprehensive study on the root extract of R. elliptica in this laboratory yielded seventeen compounds from four different classes, including 2 new pyranoanthraquinones, one new anthraquinone, eleven known anthraquinones, one lactone triterpenoid, one coumarin and one phenolic acid. The chemical profile of the root extract was established using HPLC and the selected marker compounds were used as external standards and quantified using standard calibration curve. Nordamnacanthal 5, damnacanthal 7, 2-formyl-3-hydroxy-9,10-anthraquinone 6, 2-methyl-3-hydroxy-9,10-anthraquinone 11 and 1,2-dimethoxy-6-methyl-9,10-anthraquinone 3 were determined at 3.57, 10.32, 4.47, 12.18 and 4.09 µg/g, respectively. Owing to the toxicity of dichloromethane, the extraction of the desired marker compounds was attempted using accelerated solvent extraction and soxhlet extraction using ethanol and water at different compositions. R. elliptica root extract and the isolated anthraquinones showed potential antiplasmodial activity, and the active compounds were probed for their mode of action. In addition, the dichloromethane root extract of R. elliptica and the selected anthraquinones were screened for anticancer, antioxidant, and α-glucosidase inhibitory activities as well as toxicity study in vitro.  The review summarizes the findings on Rennellia elliptica which includes phytochemistry, toxicity and its biological activities. The chemotaxonomic significance of Rennellia elliptica is also discussed